2015
DOI: 10.5301/ejo.5000594
|View full text |Cite|
|
Sign up to set email alerts
|

Choroidal and Peripapillary Retinal Nerve Fiber Layer Thickness in Adults with Anisometropic Amblyopia

Abstract: In adults with anisometropic amblyopia, subfoveal, temporal, and nasal choroidal thickness of amblyopic eyes are significantly thicker than in fellow eyes. However, no significant differences in peripapillary RNFL thickness or CMT were found between amblyopic and fellow or control eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Walker et al [ 28 ] found no significant difference in macular thickness or peripapillary RNFL thickness in patients with strabismic and anisometropic amblyopia in an adult patient population similar to ours. Kantarci et al [ 29 ] compared choroidal thickness and central macular and peripapillary RNFL thickness in adults with anisometropic amblyopia and also failed to find a difference in RNFL and central macular thicknesses, in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Walker et al [ 28 ] found no significant difference in macular thickness or peripapillary RNFL thickness in patients with strabismic and anisometropic amblyopia in an adult patient population similar to ours. Kantarci et al [ 29 ] compared choroidal thickness and central macular and peripapillary RNFL thickness in adults with anisometropic amblyopia and also failed to find a difference in RNFL and central macular thicknesses, in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Although El-Shamayleh [ 19 ] showed that the visual cortex in animals can be affected in amblyopia, advances in imaging methods and the introduction of OCT into clinical practice led to renewed attention to the retina and optic nerve in amblyopia, and the involvement of these structures was investigated extensively. Conflicting results were reported for different types of amblyopia [ 11 17 , 20 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults with anisometropic amblyopia, there was no significant difference in the subfoveal choroidal thickness between amblyopic and fellow or control eyes. [ 17 , 18 ] In children, the choroid may have greater flexibility compared to that in adults. We found that amblyopic eyes had larger luminal areas than that of normal children.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown that the choroid of anisometropic amblyopic eyes was thicker than that of fellow eyes and emmetropic control eyes . Tenlik and colleagues proposed that amblyopia might have a profound effect on choroidal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The common causes of amblyopia are strabismus, anisometropia, high bilateral refractive errors and visual deprivation. Although the reduced vision in amblyopia is conventionally explained by the abnormal neuronal network within the primary visual cortex and lateral geniculate body, recent studies have found a choroidal thickening in amblyopic eyes and suggested that there might be a relationship between the choroid and amblyopia; however, in those previous studies the amblyopic eyes were more hyperopic than the control eyes. Due to the fact that hyperopia is also associated with choroidal thickness, it is not clear whether the choroidal thickening was caused by hyperopia or amblyopia.…”
mentioning
confidence: 85%